Deiksis dalam Novel Tiba Sebelum Berangkat karya Faisal Oddang: Kajian Pragmatik - Rini Agustina Putri; Siti Ainim Liusti (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
The objectives of this study were as follows: (1) To describe the types of deixis in Faisal Oddang's novel Tiba Sebelum Berangkat; (2) To describe the context of the use of deixis types in Faisal Oddang's novel Tiba Sebelum Berangkat. This study is qualitative using a descriptive method. The data for this study were words and phrases from the novel Tiba Sebelum Berangkat by Faisal Oddang that indicate the use of deixis. The listening method, mark reading technique, and note-taking technique were used to collect data. The findings of this study are as follows. First, deixis types were discovered in the novel Tiba Sebelum Berangkat by Faisal Oddang, which were persona deixis 13 forms, place deixis 6 forms, time deixis 9 forms, discourse deixis 4 forms, and social deixis 11 forms. Second, the the characters of the novel, Mapata, Batari, Puang Matua Rusmi, Andi Upe, and Serly, are mentioned in the context of using persona deixis. The arajang house, sacred forest, and army post are all mentioned in the context of place deixis. The use of time deixis in this context refers to the morning, five days ago, and a week ago. The context in which discourse deixis is used refers to the sentence before and after. Social deixis is used in the context of bosses and subordinates, parents and children, soldiers and ordinary people, religious leaders and ordinary people.